Extraction of betalains from beta vulgaris method comparison / Hasliza Hassan - Hassan, Hasliza (2007)
The aim of this study was to extract natural pigment which is betalain in Beta vulgaris using different extraction methods. The different extraction methods used were 100% superheated water (800C), acidified superheated water (800C), acidified methanol and boiling with water (1000C). The maximum absorbance of betalain pigments were observed at λ max of 535nm and 480nm using Uv-Vis Spectrometer. These λ max of 535nm and 480nm show the presence of betacyanins and betaxanthins pigments. The extraction methods were compared using Uv-Vis at λ max 535nm. The studies show that natural pigment in Beta vulgaris can be extracted using all these methods. However, these extraction methods gave different maximum absorbance and λ max. 100% superheated water at 800C gave absorbance of 0.2070 at λ max of 533.52nm with concentration of 7.39ppm. Acidified superheated water at 800C gave absorbance of 0.2625 at λ max of 535.50nm with concentration of 9.37ppm. Acidified methanol (HCl) gave absorbance of 0.2108 at λ max of 532.06nm with concentration of 7.53ppm. Boiling with water at 1000C gave absorbance of 0.18906 at λ max of 532.06nm with concentration of 6.75ppm. From the results, the best extraction method was observed when the natural pigment was extracted using acidified superheated water at 800C as compared to other extraction methods.